Emerging Need for Academic Advising in Schools, Colleges and Universities in Kenya. - Muola, James; Mwania, Jonathan M. (International Journal of Asian Social Science, 2013)
It is not easy for the overburdened student counselors in schools, colleges and universities to adequately address students’ needs in all areas. This has led to the establishment of academic advising in Western countries and recently in some Kenyan institutions. The three common types of academic advising are developmental, prescriptive and strength-based. Findings from various studies concur that students need academic advising in time management, maintaining high grades and setting academic and career goals among other areas. Academic advising has been associated with improved academic performance and retention. Academic advising is recommended as a means of supplementing existing counseling programmes and maximizing full realization of students’ potential
Keywords: Academic; Advising; University; Need.